The avicennian understanding of the commonness of nature and its influence on John Duns Scotus - Jaramillo Gómez, María José (Perseitas, 2025)
The concept of common nature in Duns Scotus is generally recognized for taking inspiration from the same concept of the philosopher Avicenna. While the proposals of the philosophers regarding common nature are similar, the difference between them and the contributions made by Scotus may not be immediately clear. This article examines the profound influence of Avicenna’s proposal on Scotist theory and elucidates Scotus’ contributions and the evolution of the concept of common nature from a Scotist perspective. This study explores the questions: Is Scotus’ theory simply a reflection of Avicenna’s proposal? And what are the contributions that Scotus introduces to the concept of common nature that were previously presented by Avicenna? The article will demonstrate that Scotus adds valuable ideas to the concept of common nature that were not initially present in Avicenna’s proposal, which helps create a clearer distinction between the common and the universal and will eventually serve as the basis for the realist epistemology proposed by Scotus and his views on the understanding of reality and its relationship with knowledge.